The Definition, Understanding and Treatment of Echoism Using the Daseinsanalytic Model of Alice Holzhey-Kunz (Existential Analysis: Journal of the Society for Existential Analysis, 2020)
Holzhey-Kunz's Daseinsanalytic approach facilitates an understanding of the ontological dimension in work with echoists. Case material demonstrates how the approach allows further understanding of echoism. The concept of Hellhörigkeit, the ontico-ontological distinction of Heidegger, and the ideas of Kierkegaard and Sartre, have contributed to a greater understanding of echoists.
Keywords: Echoism; Daseinsanalysis; Hellhörigkeit; ontico-ontologicaldistinction; ontological anxiety; ontological guilt; The Look; Echoistic-Narcissistic complex